OPTIMIZATION OF ASIAN CLAM POSITIONING MODEL FOR IMPROVED WATER QUALITY IN NILE TILAPIA CULTURE UNDER THE YUMINA BUMINA SYSTEM - Alexander Burhani Marda; Risca Permatasari; Ayutha Wijinindyah; Gusti Muhamad Juriansyah Febrianor; Sandy Indra Saputra; Laila Uswatun Hasanah; Yuliana Yuliana (Universitas Mataram, 2025)
The Yumina Bumina aquaponic system an indigenous innovation grounded in Integrated Multi-Trophic Aquaculture (IMTA) offers a sustainable approach to Nile tilapia (Oreochromis niloticus) cultivation through the integration of water spinach (Ipomoea aquatica) and the freshwater mussel Anodonta woodiana. This study aimed to evaluate the effects of four spatial configurations of A. woodiana on water quality and tilapia growth over a 30-day period. A Completely Randomized Design was employed with four treatments: (A) mussels positioned upstream of the plant unit, (B) downstream of the plant unit, (C) within the recirculation pipe, and (D) an integrated configuration combining all positions, with outcomes subjected to rigorous statistical analysis. Results indicated that although Treatment C yielded the lowest ammonia concentration (1,10 ± 0,85 mg/L), Treatment A achieved the highest daily weight gain (15.74%/day) and the lowest total dissolved solids (TDS; 388,4 ppm). Conversely, Treatment C led to the highest nitrite accumulation (3,74 mg/L) and elevated TDS levels, posing a potential risk of osmoregulatory stress in fish. No significant differences were observed in %Total N content in either tilapia or water spinach across treatments (*p* > 0.05), indicating that growth variation was primarily driven by physiological environmental stability rather than nitrogen availability. These findings confirm that positioning A. woodiana as a pre-filter upstream of the plant zone (Treatment A) establishes an optimal, gradual nutrient flow, minimizes environmental stress, and maximizes fish growth. This study provides strategic hydraulic design recommendations for sustainable, IMTA-based aquaponic systems.